Investigation of the flow characteristics of slit check dams using novel models - Emiroglu, Muhammet Emin; Ikinciogullari, Erdinc; Yalcin, Eyyup Ensar; Gul, Enes (Springer Heidelberg, 2024)
Floods, which cause loss of life and property and destruction of the environment, have devastating effects on socio-economic welfare. Slit-check dams are essential structures for managing the transport of silt and woody debris, especially in events of significant floods. The current study presents the hydraulic characteristics of slit-check dams with different geometries for experimental and numerical tests. First, the Butterfly model was produced with a 3D printer and examined experimentally. Then, the Butterfly model was validated extensively using OpenFOAM (v7) software for the numerical analysis. Finally, the other models were examined numerically using the k-epsilon turbulence model. The changes in water surface profile, velocity profiles, energy dissipation rates, and streamlines were comprehensively examined and discussed. The results showed that slit-check dams caused hydraulic jumps and dissipated flow energy. The Arced and Rectangular models, in particular, demonstrated a significant performance for energy dissipation, which is essential for flood management. Water surface profiles are directly affected by discharge. Moreover, the cross-sectional length of the model in question significantly affects the water surface profile. Accordingly, an increase was observed in the velocity profiles along the slit-check dam. While the maximum velocity for all unit discharge was observed in the V-shaped model, the minimum velocities were observed for the Arced and Rectangular models. Thus, the energy absorption performance of Arced and Rectangular models is higher.
Keywords: Flood; Flood control structure; Slit-check dam; Debris flow; Torrential barrier; OpenFOAM; Computational Fluid Dynamics (CFD)